Inside Cover: Singlet Fission in Carbene‐Derived Diradicaloids (Angew. Chem. Int. Ed. 20/2020). Issue 20 (6th April 2020) - Ullrich, Tobias; Pinter, Piermaria; Messelberger, Julian; Haines, Philipp; Kaur, Ramandeep; Hansmann, Max M.; Munz, Dominik; Guldi, Dirk M.
Abstract : The plasmon‐induced dissociation of a single O2 molecule strongly chemisorbed on a silver surface was investigated by using a scanning tunneling microscope combined with an optical set‐up for light irradiation, as reported by Y. Kim et al. in their Research Article on page 7960 . Analyses of the single‐molecule reaction and the electronic structure responsible for the reaction revealed that the hot carriers generated through the decay of the plasmon are transferred to the antibonding (π*) orbitals of O2, which are strongly hybridized with the metal states.